Evaluasi Status Kesuburan Tanah untuk Lahan Pertanian di Kecamatan Denpasar Timur - WIDYANTARI, DYAH AYU GEDE; SUSILA, KETUT DHARMA; KUSMAWATI, TATIEK (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.4, No.4, Oktober 2015, 2016)
ABSTRACT Evaluation of Soil Fertility Status for Agricultural Land at East Denpasar District   Research on Evaluation of Soil Fertility Status for Agricultural Land in East Denpasar District was conducted in January-July 2014. The purpose of this study was to analyze some soil chemical properties that become obstacles soil fertility status, evaluate and map the soil fertility status of the study area. The method used in this study include, methods of survey and soil testing in the Soil and Environment Laboratory, Faculty of Agriculture, Udayana University. The study begins with  the manufacture of the land unit map by clicking the map overlay-type of soil; map slope; and land use maps. Retrieved five land units and each of land units were taken the composite soil samples and analyzed its chemical properties in the laboratory which includes CEC; KB; C-organic; total – P and K of soil. Further evaluation of soil fertility status corresponding technical instructions of Soil Research Center, Bogor (1995).           The results showed that the soil in the study had two soil fertility status, namely the status of medium and low soil fertility. The location study which has the status of soil fertility was covering land unit T1a; T1b; and T1c at Padang Galak Subak Kesiman Kertalangu (Kesiman Village, Kesiman Kertalangu Village, and Kesiman Petilan Village); T1d on Subak Yeh Lauh (Penatih Village), T3 land unit (Kesiman Kertalangu Village and Penatih Dangin Puri Village), and land units T4 on Subak Semaga (Penatih Village), While the research sites that have low fertility status covering, land unit T2 on Subak Delod Sema (Kesiman Village) and T5 land unit (Penatih Dangin Puri Village). Parameters of soil fertility is a constraint in dermining the fertility status of the soil, in the low content of  C-organic and total-P of soils. Management referral of soil fertility for the land unit T2 and T5 to suggest the addition of organic matter and fertilizer P to improve soil fertility status. Key Words : Soil fertility status; land units; agricultural land; East Denpasar District